Experiential Learning in Journalism Education: A New Zealand Case Study - Boyd-Bell, Susan (Auckland University of Technology, 2008)
Teaching journalism in tertiary institutions presents challenges, including how students learn to work in teams under the sort of pressure that characterizes workplace journalism. This thesis is a case study of how a group of students at AUT University, in Auckland, experienced taking responsibility for producing four editions of a student newspaper as part of their journalism training. Based on a series of individual student interviews, before, during and after their experience, this research suggests that the key factor in their learning was their being allowed, to a large extent, the power to make their own decisions about the appearance and content of their product, while still being charged with the responsibility of ensuring it reached a highly professional standard. The realities of life as a journalist, including recognizing the frequent need to prune, tighten or re-angle stories - even to reject them - and the vital role of co-operative teamwork, unparalleled in their other journalism studies, were driven home. The two tutors, interviewed after the last edition, put some of the student observations into context and provided insights into the discipline involved, as teachers, in maintaining training as a priority, while ensuring production to deadline of a series of reputable and legally safe newspapers. This case study suggests that while there are contrived aspects that cannot replicate a "real" newsroom - such as the students' assignment to editorial roles without the status of real editors or chief reporters - the learning experience resulted not only in advances in the students' technological skills but significant development in their critical thinking about the profession they were due to enter.
Keywords: Journalism education; Experiential learning; Problem-based learning; Student empowerment; Student newspaper; Structured interviews